Investigating the structure of the factor B vWF-A domain/CD55 protein-protein complex using DEER spectroscopy: successes and pitfalls. - Lovett, J; Abbott, R; Roversi, P; Johnson, S; Caesar, J; Doria, M; Jeschke, G; Timmel, C; Lea, S (2013)
The electron paramagnetic resonance technique of double electron-electron resonance (DEER) was used to measure nanometre-scale distances between nitroxide spin labels attached to the complement regulatory protein CD55 (also known as decay accelerating factor) and the von Willebrand factor A (vWF-A) domain of factor B. Following a thorough assessment of the quality of the data, distances obtained from good-quality measurements are compared to predicted distances from a previously hypothesised model for the complex and are found to be incompatible. The success of using these distances as restraints in multi-body docking routines is presented critically.